SOCIAL RISK MODELING AT AIRPORTS: ON THE EXAMPLE OF ZAPORIZHZHIA CITY - Honcharova, Valeriia (Fırat University, 2021)
The aviation sector is in constant relationship with society and the social sphere at all levels. The airport acts as an entrance and exit gate from one sphere, region, country to another, and must ensure safety, good management and prevent possible risks. Therefore, airports should carry out activities related to the implementation of social modeling and use related methods. Now the state of the aviation sector in Ukraine is in a difficult situation, one of the main factors is the conditions of the COVID-19 pandemic, therefore, in the post-pandemic conditions, airports have to worry about their strengths/weaknesses, opportunities and threats for developing development strategies. The object of our research is the global risks at airports. The subject of our article is the social modeling of risks at airports using the example of the COVID-19 pandemic. The purpose of the article is to investigate the main contexts of social risk modeling at airports for the conditions of the COVID-19 pandemic at the airport in Zaporizhzhia. The airport risk modeling research methodology was defined by a systematic approach (system research stages) and synergy research. Qualitative research methods are the FORESIGHT complex and the use of strategic forecasting of desk analysis methods in combination with SWOT/STEEP/TOWS methods, which makes it possible to obtain possible scenarios. Results. The introduction of social modeling can ensure the prevention of risks, threats and affect the strategic development of airports and the safety of air communications (for example Zaporizhzhia city).

Havacılık sektörü her düzeyde toplumla ve kamusal yapıyla sürekli ilişki içindedir. Havalimanı bir alandan, bölgeden, ülkeden diğerine giriş ve çıkış kapısı görevi görür. Hava limanının güvenliği, iyi yönetimi sağlamalı ve olası riskleri önlemelidir. Bu nedenle havalimanları sosyal modellemenin uygulanması ile ilgili faaliyetlerde bulunmalı ve ilgili yöntemleri kullanmalıdır. COVİD-19 koşulları nedeniyle Ukrayna'da havacılık sektörü çok zor durumdadır. COVID-19 pandemisinin koşulları ve pandemi sonrası koşullarda havalimanlarının güçlü/zayıf yönleri, fırsatları hakkında sratejiler geliştirmeli ve tehditleri öngörmelidir. Araştırmamızın amacı havalimanlarındaki küresel risklerdir. Makalemizin konusu, COVID-19 pandemisi örneğini kullanarak havalimanlarındaki risklerin sosyal modellemesidir. Makalenin amacı, Zaporizhzhia'daki havaalanında COVID-19 salgını koşulları için havaalanlarında sosyal risk modellemesinin ana bağlamlarını araştırmaktır. Havaalanı risk modelleme araştırma yöntemi sistematik bir yaklaşım (sistem araştırma aşamaları) ve sinerji araştırması ile tanımlanmıştır. Nitel araştırma yöntemleri, FORESIGHT kompleksi ve olası senaryoların elde edilmesini mümkün kılan SWOT/STEEP/TOWS yöntemleriyle birlikte stratejik tahminlerinin kullanılmasıdır. Sonuç olarak, Zaporizhzhia şehri örneği üzerinden sosyal modellemenin tanıtılması, havaalanları açısından risklerin, tehditlerin önlenmesini sağlayabilir ve havaalanlarının stratejik gelişimini ve hava iletişiminin güvenliğinin geliştirilmesine olumlu katkıda bulunabilir.
Havaalanlarında Sosyal Risk Modellemesi: Zaporizhzhia Şehri Örneği Üzerine